Indoor thermal environment during heating season and the health of elderly in China. (9th August 2022) - Song, Bai; Yoshino, Hiroshi; Goto, Tomonobu; Zhang, Huibo; Guan, Jun; Hasegawa, Kenichi; Kagi, Naoki; Li, Nianping; Li, Zhenhai; Liu, Jing; Lv, Yang; Xie, Jingchao; et al.
Abstract : In this study, questionnaire surveys and field measurements were conducted at houses with elderly people in urban and rural areas across six regions of China. The prevalence of hypertension was approximately 40% in both urban and rural areas. The logistic analysis results indicated a greater prevalence of hypertension in the elderly of rural residences and a low indoor temperature-induced hypertension. According to the field measurement survey, the room temperature was stable at around 23 °C in the housing in northern urban areas equipped with district heating systems, and fluctuated from being equivalent to outdoor temperature to around 15 °C in the southern regions where air-conditioners were used. For housing in the northern rural areas where Chinese Kangs were used, the daily fluctuation in room temperature was significant, and room temperature was stable at a low level in the southern part without space heating. The room temperature and blood pressure were negatively correlated. Therefore, to maintain the health of the elderly in houses with low room temperatures in winter, it is necessary to improve the thermal environment by enhancing the thermal performance of the building and the heating equipment.